Nursing Care of Clients with Pulmonary Tuberculosis with Ineffective Airway Cleaning in General Hospitals Koja area, North Jakarta - Ragil Supriyono; Memed Sena Setiawan (JOURNAL EDUCATIONAL OF NURSING(JEN), 2022)
Tuberculosis (TB) is a chronic infectious disease caused by the bacterium Mycobacterium tuberculosis. This bacterium is rod-shaped and is acid-resistant, so it is known as Acid-resistant Bacilli (BTA). Pulmonary Tuberculosis (TB) on the 8th floor of Block B at Koja Hospital, North Jakarta, from the last 6 months there has been an increase, obtained from data on the number of tuberculosis patients in July 2017, 324 people. This study aims to determine the comparison of the three respondents, namely client 1 (Mrs.M) and client 2 (Mrs.Y), Client 3 (Mr.D) correctly performs Deep Breathing and Effective Coughing on the independence of Pulmonary Tuberculosis patients. The research method is descriptive with a case study approach, namely by carrying out nursing care in Pulmonary Tuberculosis (TB) starting from assessment, intervention, implementation and evaluation of nursing. And data collection can be carried out for 6 days at Koja North Jakarta Hospital. Data analysis requires further treatment and collaboration with other medical teams, clients and families which are very necessary for the success of nursing care. It can be seen from the variable results on Nursing Care of Pulmonary Tuberculosis (TB) patients. It can be seen from the results of independent activity variables doing Deep Breathing and Effective Exhalation correctly.